Fibromyalgia and its Approach in Clinical Repertories (Advancements in Homeopathic Research, 2023)
Fibromyalgia is a condition which has widespread  musculoskeletal pain with fatigue, cognitive  disturbance, psychiatric and multiple somatic  symptoms. There is no evidence of tissue inflammation  despite symptoms of soft tissue pain. This article  deals with clinical presentation of fibromyalgia as  well as its approach in clinical repertories which are  commonly used like Boreicke repertory and Phatak  repertory.
Keywords: Homeopathy; Fibromyalgia; Clinical repertories; Phatak repertory; Boericke repertory